Distribution Characteristics of Pyralid Moths (Lepidoptera: Pyralidae, Crambidae) in the Agroecosystems of the Fergana Valley - Shermatov Malikjon Rakhmatjonovich; Botirov Elyor Arabboyevich; Abdikakhorov Bekzod Dilmurod o’g’li (Zien Journals, 2022)
The article presents a characteristic of the distribution of moth butterflies (Pyralidae, Crambidae) in agrocenoses of the Ferghana Valley by plant families and life forms. 22 species of butterflies have a trophic relationship with 30 species of cultivated plants belonging to 10 families. There are 18 species in cultivated herbaceous plants, 3 species in trees, and 1 species in shrubs.
Keywords: Pyraloidea; Pyralidаe; Crambidae; butterfly